Eksplorasi Variabel Jenjang Pendidikan Dalam Mempengaruhi Efektivitas Flipped Classroom Terhadap Prestasi Akademik Siswa - Hukom, Julham (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to explore the influence of educational level on the effectiveness of flipped classroom in improving students' academic achievement. The method used is Integrative Literature Review, which analyzes various studies related to the implementation of flipped classroom at various levels of education, including primary, secondary, and tertiary education. The main findings indicate that flipped classroom can improve students' understanding of the material and academic achievement at all levels of education, with a more significant impact on secondary and tertiary students. However, the effectiveness of this model depends on factors such as students' digital skills, teacher readiness, and adequate access to technology. This study recommends that further research be conducted to explore the adaptation of flipped classroom in different geographical and cultural contexts, as well as to evaluate the long-term impact of implementing this model at various levels of education.